Identification of the SP22 Sperm Protein in Santa Ines and Dorper Rams - Favareto, A. P. A. [UNESP]; Rodello, L. [UNESP]; Taconeli, C. A. [UNESP]; Bicudo, Sony Dimas [UNESP]; Klinefelter, G. R. [UNESP]; Kempinas, W. G. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
ContentsThe sperm membrane protein referred to as SP22 has been identified in different species and, at least in rats, is highly correlated with fertility. The goals of this study were to identify and to quantify the SP22 protein on spermatozoa from adult rams (Dorper and Santa Ines breeds), and to correlate its levels to morphological and kinematics parameters. SP22 on ram sperm was effectively quantified by both enzyme-linked immunosorbent assay (ELISA) and fluorescein isothiocyanate immunostaining analysis and the two methods were significantly correlated (R2 = 0.70). Clustering analysis of motility parameters obtained by computer-assisted semen analysis system was used to establish that three distinct kinematic subpopulations with different vigour and progressiveness coexistent within ejaculate. While there were significant differences in the distribution of the three subpopulations in the rams, there was no significant correlation between the proportion of each subpopulation in the rams and the SP22 levels. Quantification of SP22 immunostaining intensity was not correlated with any of the sperm parameters. However, SP22 levels obtained by ELISA were negatively correlated with morphological abnormalities and positively correlated with membrane integrity (three variable R2 = 0.47). Future breeding studies are now needed to validate that this protein is a biomarker of fertility in this species.